Alternative Settlement of Dispute Results for the Election of Village Head to Realize Democracy in South Buton - Indah Kusuma Dewi; Luh Putu Sudini; Hardin; Faais Mufaasir Ramadhan (Sociological Jurisprudence Journal, 2022)
The emergence of prolonged Village Head Election Conflicts due to fanaticism and the harsh confrontation of supporters of the village head candidates who face to face fight for the victory of their respective candidates. Sometimes they even forget the value of democracy and undermine the ethical values ​​that have been embedded in village communities. The purpose of this study was to determine the resolution of the dispute over the election results of the Lawela Village Head in realizing democracy in South Buton and to find out the legal consequences of the South Buton Regent's decision on the cancellation of the results of the Lawela Village Head election, South Buton Regency. The method used in this research is normative juridical. The stages of the research method are preparation and administration, inventory of relevant laws and regulations, research, analysis of research results, preparation of research reports and Focus Group Discussion. Based on the above explanation, the legal consequence of the South Buton Regent's Decree Number 341 of 2019 concerning the Dispute Resolution of the Election Results of the Lawela Village Head, Batauga District, South Buton Regency in 2019 is that the results of the Lawela Village Head election in the Lawela Village Head Election become non-binding from the moment it is canceled or fixed. The legal consequences for the elected Village Head candidate in Lawela Village are being canceled as the elected Village Head candidate or as Lawela Village Head for the 2019-2015 periods and/or as the winner who has succeeded in obtaining the most votes based on the determination of the Lawela Village Head Election Committee in 2019.